Predictive value of monocyte-to-high-density lipoprotein-cholesterol ratio (MHR) for poor prognosis after intravenous thrombolytic therapy for acute ischaemic stroke - Yinglei Li; Lingyun Xi; Litao Li (Archives of Medical Science)
Introduction The purpose of this study was to examine the relationship between monocyte-to-high-density lipoprotein-cholesterol ratio (MHR) and poor short-term 3-month and long-term 6-month prognosis after intravenous thrombolysis in patients with acute ischaemic stroke.